2009
DOI: 10.1210/jc.2009-0609
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants ofTCF7L2Are Associated with Insulin Resistance and Related Metabolic Phenotypes in Taiwanese Adolescents and Caucasian Young Adults

Abstract: These findings support an important role for T2D risk-conferring gene TCF7L2 in insulin resistance in both Taiwanese and Caucasian youth and underscore the emerging role of Wnt signaling in insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 36 publications
5
46
1
Order By: Relevance
“…HOMA2-IR was significantly higher in patients with rs290487 C/C variant homozygote than those with T/T or T/C genotypes. This result was consistent with a previous study, which revealed that rs290487 C allele was significantly associated with increased IR in both Taiwanese and Caucasians (Chang et al, 2010;Liu et al, 2009). Since HD is characterized by very high IR compared to type 2 diabetes (Garcia-Compean et al, 2009), the association between TCF7L2 genetic variant and increased IR may help us to understand the mechanism of HD.…”
Section: Discussionsupporting
confidence: 93%
“…HOMA2-IR was significantly higher in patients with rs290487 C/C variant homozygote than those with T/T or T/C genotypes. This result was consistent with a previous study, which revealed that rs290487 C allele was significantly associated with increased IR in both Taiwanese and Caucasians (Chang et al, 2010;Liu et al, 2009). Since HD is characterized by very high IR compared to type 2 diabetes (Garcia-Compean et al, 2009), the association between TCF7L2 genetic variant and increased IR may help us to understand the mechanism of HD.…”
Section: Discussionsupporting
confidence: 93%
“…Accumulated β-catenin translocates to the nucleus, where it binds to TCF/LEF transcription factors to activate the transcription of Wnt-responsive genes involved in cell proliferation and differentiation [29]. Various studies have demonstrated an association of TCF7L2 variants with features of metabolic syndrome, including elevated systolic and diastolic blood pressure, increased triglyceride levels, and elevated uric acid [30,31]. Recently, the activation of Wnt/β-catenin signaling in skeletal muscle cells was reported to improve insulin sensitivity by decreasing intramyocellular lipid deposition via downregulation of SREBP-1c [19].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is uncertain, with some studies reporting that risk genotype is associated with defective insulin secretion (2,2325). Some studies have reported an association with a decreased insulin action (8,26), and others have reported both (27). The present studies measured insulin secretion and insulin action in a large number of subjects with the TT genotype on three separate occasions and compared the results to those observed in carefully matched subjects with the CC genotype.…”
Section: Discussionmentioning
confidence: 99%